PENGGUNAAN MODEL EXPERIENTIAL LEARNING DALAM KETERAMPILAN MENULIS PARAGRAF ARGUMENTASI MAHASISWA JURUSAN PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Ida Ayu Made Darmayanti; I Gede Nurjaya; I Nengah Martha; I Nyoman Sudiana (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2018)
The main objective of this research is to describe the achievement of the Indonesian LanguageEducation students after using the experimental learning method in writing argumentative paragraphand also to find out the obstacles faced when using that learning method. The subject of this study werethe students of Indonesian Language Education Department. The data of this study were collected byusing two methods, they were assignment method and interview. The data collected were analyzed by usingdescriptive qualitative research design. Besides, the aims of this study are that; first, to improve thelearning quality in writing argumentative paragraph. Second, this study is in order to keep the existenceof experimental learning method, and the last one is to persuade and motivate the students to be morecreative and innovative. The result of this study indicated that the achievement of Indonesian LanguageEducation students when using this method was categorized in the highest level that was 90.56 points.And the obstacles found by the Indonesian Language Education students in using this experimentallearning method related with their creativity in writing argumentative paragraph are that; first, theyhave limited information about how to organize the sentences well; second, it is hard for them to find thekey words when they start to make a sentence; and the last one is that not all of them are able to use thespelling order perfectly.Keywords: Experimental Learning Method, writing creativity, argumentative paragraph